2004
DOI: 10.1255/jnirs.439
|View full text |Cite
|
Sign up to set email alerts
|

Non-Destructive Determination of Carbohydrate Content in Potatoes Using near Infrared Spectroscopy

Abstract: The performance of near infrared spectroscopy as a simple technique for the non-destructive determination of carbohydrate content in potatoes was examined. An interactance method was adopted to measure near infrared spectra (700-1100 nm). A good calibration model with reasonable accuracy (correlation coefficient of 0.93 and standard error of prediction of 0.98%) was developed using partial least square (PLS) regression. The PLS calibration model utilised effectively two characteristic absorption bands of 990 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…A total of 15 PLS calibration models were developed for analyzing frying oils using the calibration and validation sample sets. There was a strong correlation between the NIR predicted data and validation data, (Williams, 2001;Chen et al, 2004Chen et al, , 2005Chen et al, & 2007. It can be concluded that the NIR spectra provided a good estimation of AV in frying oils, particularly for spectra that showed a low SEP value and a high RPD value.…”
Section: Nir Models For Av Pls Regression Results For Predicting Avmentioning
confidence: 74%
See 1 more Smart Citation
“…A total of 15 PLS calibration models were developed for analyzing frying oils using the calibration and validation sample sets. There was a strong correlation between the NIR predicted data and validation data, (Williams, 2001;Chen et al, 2004Chen et al, , 2005Chen et al, & 2007. It can be concluded that the NIR spectra provided a good estimation of AV in frying oils, particularly for spectra that showed a low SEP value and a high RPD value.…”
Section: Nir Models For Av Pls Regression Results For Predicting Avmentioning
confidence: 74%
“…predicting TPC values in frying oils using NIR spectra are shown in Table 3 et al, 1989;Chen et al, 2004Chen et al, , 2008. In order to determine characteristic peaks and troughs in a regression coefficient spectrum, we observed and discussed the regression coefficients of PLS regression models based on secondderivative spectra.…”
Section: Nir Models For Tpc Values Pls Regression Results Formentioning
confidence: 99%
“…NIR calibration and prediction results for the total protein content and protein composition of rice flour samples. wavelengths to a PLS calibration model, since a regression coefficient spectrum shows characteristic peaks and troughs that can indicate which wavelength range is important for the calibration model (Martens et al 1989;Chen et al 2003Chen et al , 2004. Figure 4 shows the regression coefficients of the PLS calibration models of total protein (a), prolamin component (b), globulin component (c) and glutelin component (d), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The first-and secondderivative spectra (Duckworth 2004;Chen et al 2003Chen et al , 2004 were obtained by the Savitsky-Golay method (Madden 1978) with a segment of 20 nm and a gap of 0 nm. The PLS regression and derivative mathematical treatments were carried out using the Unscrambler Ver.7.6 software.…”
Section: Discussionmentioning
confidence: 99%